Pengaruh Metode Silabe Berbantuan Media Roda Suku Pintar terhadap Keterampilan Membaca Permulaan Siswa Kelas 1 di SDN 4 Cakranegara - Astika Rizki; Muhammad Sukri; Nurwahidah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to determine the effect of the syllabe method assisted by the Smart Tribe Wheel media on the beginning reading skills of first-grade students at SDN 4 Cakranegara. This study uses a quantitative research method of the Quasi Experimental type with a Non-Equivalent Control Group Design. The sample in this study was determined by a saturated sampling technique, where class 1A was designated as the control group and class 1B as the experimental group. The data collection process was carried out through tests and observations, then the data obtained were analyzed using the Independent Sample t-Test. The results of the analysis showed that the t-count value of 2.221> t-table value of 2.018, so the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Based on these results, it can be concluded that the application of the syllabe method assisted by the Smart Tribe Wheel media has a significant effect on the beginning reading skills of first-grade students at SDN 4 Cakranegara.